Restorative Justice in Criminal Law Enforcement from a Legal Perspective as a Social Engineering Tool - Aruan, Thommy (AIBPM Publisher, 2024)
Restorative justice has emerged as an alternative approach in criminal law enforcement that regards crime as a violation of the relationship between the individual and society, not just as a crime against the state. This study investigates the concept of restorative justice in the context of criminal law enforcement, focusing on the perspective of law as a tool of social engineering. From the point of view of the law as the tool of social engineering, this study explains how restaurative justice is applied in Indonesia in relation to criminal law. The conclusion of this study is that it is necessary to reconstruct the establishment of restorative mechanisms ranging from the stages of mediation, divorce, to rehabilitation and supervision. This research provides an in-depth understanding of the concept of restorative justice in the context of criminal law enforcement, emphasizing the vital role of law as a social engineering tool for achieving desired goals.